MODEL USAHATANI KENTANG DI HULU DAERAH ALIRAN SUNGAI (DAS) CITARUM (Studi Kasus di Koperasi Pertanian Pesantren Al-Fatah) - Andrini, Raissa Fidela; Setiawan, Iwan (Universitas Galuh Ciamis, 2020)
Kertasari Subdistrict is the area with the largest critical land in Bandung Regency. Critical land is due to changes in the use of forest land into the cultivation of annual crops and settlements. The objective to be achieved in this research is to describe the seasonal farming model, namely potatoes in the upstream Citarum watershed which are cultivated continuously. The research design used in this research is qualitative and the research technique used is case study. The farming model in Kertasari Subdistrict is still conventional farming, which uses agricultural tools and uses human and animal power. Koppotran has his own land and rental land accompanied by conservation techniques on sloping land. Potato plants are actually not environmentally friendly because they damage the environment such as erosion and for reforestation Kopottran is doing intercropping with coffee plants and cleaning the Citarum watershed. The community must increase their awareness of environmental sustainability by reforestation around the settlement and Citarum watershed.